Study of Traditional Drug Ethnopharmacology Used for The Treatment of Metabolic Disorders in Pamona Puselemba District - Andi Atirah Masyita; Arwinda Alitsia Hasyim; Yuliet Yuliet; Ritha Pratiwi (JOURNAL OF NONCOMMUNICABLE DISEASES, 2023)
People in Pamona Puselemba Subdistrict in Poso Regency have used various plant species to maintain health and prevent various diseases, one of which is metabolic disorders. This study aims to determine the types and parts of plants, processing methods, use, duration of treatment, frequency of use, and chemical content contained in plants that are efficacious as drugs for metabolic disorders. The research was conducted descriptively using qualitative methods and the technique of taking informants (Hattra and sufferers) with the purposive sampling method. The results obtained were 32 types of plants, consisting of 24 families, for the treatment of metabolic disorders. The plant parts used were 49% leaves, 12% stems, 21% fruit, 6% tubers, 3% flowers, 3% rhizomes, 3% seeds, and 3% hair. Processing method: 77%, blended, brewed 13%, without processing 77%. How to use: drink 89%, eat directly 11%, duration of treatment 1 week, and frequency of use 2 times a day. The content of compounds contained in medicinal plants is very diverse, such as flavonoids, terpenoids, saponins, tannins, alkaloids, allisin, and other chemical compounds that can be used in the treatment of metabolic disorders. People in Pamona sub-district still use traditional medicine to treat metabolic diseases.